2010
DOI: 10.1098/rspb.2010.0206
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2affects shell dissolution rate but not calcification rate in a marine snail

Abstract: As CO 2 levels increase in the atmosphere, so too do they in the sea. Although direct effects of moderately elevated CO 2 in sea water may be of little consequence, indirect effects may be profound. For example, lowered pH and calcium carbonate saturation states may influence both deposition and dissolution rates of mineralized skeletons in many marine organisms. The relative impact of elevated CO 2 on deposition and dissolution rates are not known for many large-bodied organisms. We therefore tested the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 30 publications
4
63
0
2
Order By: Relevance
“…Decreased size and thickness of mussels has resulted from elevated pCO 2 , including during larval stages [26]. There are also an increasing number of studies that show decreased growth in shell area with decreasing pH (see review in [15]), sometimes as a result of net dissolution [46] and reduced shell density [47]. Melzner et al [48] recorded dissolution internally in a congener (M. edulis) of our focal species, though we note that M. edulis has an aragonitic inner layer that is more susceptible to dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased size and thickness of mussels has resulted from elevated pCO 2 , including during larval stages [26]. There are also an increasing number of studies that show decreased growth in shell area with decreasing pH (see review in [15]), sometimes as a result of net dissolution [46] and reduced shell density [47]. Melzner et al [48] recorded dissolution internally in a congener (M. edulis) of our focal species, though we note that M. edulis has an aragonitic inner layer that is more susceptible to dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…This confirmed the results of Beniash et al (2010) and Welladsen et al (2010) on oysters, showing that the ultrastructure and the mechanical properties of the shells were significantly altered under high CO 2 . Nienhuis et al (2010) have shown that the growth of the rocky intertidal snail Nucella lamellosa decreases with increasing pCO 2 levels as a consequence of increased dissolution rates. This suggests that gross calcification was not impacted.…”
Section: Calcification and Shell Growthmentioning
confidence: 99%
“…For instance, CO 2 driven acidification can cause reductions in CaCO 3 saturation, making calcification more energetically costly for individuals relying on aragonite and calcite (Feely et al, 2004). Under-saturation of CaCO 3 therefore increases the risk of fast rates of shell dissolution, at which recovery may not take place (Nienhuis et al, 2010). In addition, seawater magnesium carbonate (MgCO 3 ) may also become under-saturated because of carbonate chemistry changes in seawater.…”
Section: Introductionmentioning
confidence: 99%
“…ocean warming, "OW") and in carbonate chemistry and pH driven by increasing CO 2 emissions (i.e. ocean acidification, "OA") (IPCC 2014) are known to impact the integrity and morphology of the shell of adult marine organisms (Nienhuis et al, 2010;Thomsen et al, 2010;Melatunan et al, 2013). Some defence mechanisms such as decreased shell growth rates to preserve energy (Findlay et al, 2010) and increased calcification in a range of calcifying species across taxa have been observed in acidified conditions (Ries et al, 2009).…”
Section: Introductionmentioning
confidence: 99%